Auditor judgment in the fourth industrial revolution - Samiolo, Rita; Spence, Crawford; Toh, Dorothy (Contemporary Accounting Research, 2024)
Abstract Discourse proclaiming the advent of a fourth industrial revolution predicts significant disruption to various work domains in the near future. Auditing is one of the domains where bold claims about the potential of technology are being made, with technology expected to augment auditors' judgments and, in time, possibly automate them. Drawing on 44 in‐depth interviews with auditors, regulators, and emergent artificial intelligence software providers, we question the prevailing narrative around technological change in auditing which suggests that ostensibly simple, low‐level technical tasks are areas where little judgment is at play and thus are ripe for automation. We show that significant elements of deliberation, sensemaking, and reflexivity, arguably critical for the socialization of early career auditors into the profession, may be lost when automating areas of work perceived as low value, leading us to question what it means to apply judgment in auditing. Conversely, higher‐level aspects of the audit process may be assisted by technology and augmented in different ways, yet new technological structures generate new areas of indeterminacy that pose new and yet unresolved demands on auditors' judgment. Overall, the paper shows how auditor habits are changing and highlights the risks posed by new technologies to the acquisition of practical knowledge by auditors.